(untitled) (Biological Sciences - PJSIR, 2003)
Wheat breads supplemented with different oilseed flours were evaluated for nutritive value and for acceptability by sensoric subjective analysis. It was found that protein content of bread increased from I 1.2 to 22.30% ,vi!h supplementation of soy bean and 11.2 to 21.50% with peanut flours. Variation in other nutrients also observed. Sensoric evaluation revealed highest acceptability rating for soybean flour (7.3-6.8) based bread followed by peanut flour (7.2-6.4).